2017
DOI: 10.3109/13668250.2017.1327039
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and challenging behaviour in adults with intellectual disability: A systematic review

Abstract: The present review is part of a larger study into challenging behaviour supported by an NIHR HTA grant ref 10/104/13.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
(82 reference statements)
0
14
2
Order By: Relevance
“…Our finding (based on meta-analysis of pooled data from 10 studies) of a significant intergroup difference differs from that of other systematic reviews, [19][20][21] which found no such difference. Our finding has to be interpreted with caution.…”
Section: Interpretation Of Meta-analyses Findingscontrasting
confidence: 99%
See 1 more Smart Citation
“…Our finding (based on meta-analysis of pooled data from 10 studies) of a significant intergroup difference differs from that of other systematic reviews, [19][20][21] which found no such difference. Our finding has to be interpreted with caution.…”
Section: Interpretation Of Meta-analyses Findingscontrasting
confidence: 99%
“…Three systematic reviews looked at the association between challenging behaviour and epilepsy in people with intellectual disabilities: none of these found any association. [19][20][21] We decided to carry out an updated systematic review, as important publications either have appeared since the last reviews or were not included in those reviews. Another reason for carrying out this review is to conduct meta-analyses that were not done in any of the previous reviews.…”
Section: Previous Systematic Reviews On the Subjectmentioning
confidence: 99%
“…Matson & Boisjoli () found that the majority of CB is sustained by multiple factors. This has been highlighted continuously (Ayres, ; Blickwedel, Ali, & Hassiotis, ; Bromley, Emerson, & Caine, ; Brylewski & Wiggs, ; Chatterton, ; Matson & Neal, ; O’Dwyer & Friedman, ; Taylor, Rush, Hetrick, & Sandman, ).…”
Section: Introductionmentioning
confidence: 98%
“…In people with intellectual disability presenting with challenging behaviour, it is important for the treating clinician to rule out seizure activity given the high rate of seizure disorder as a comorbidity in this group (Blickwedel et al, 2017;Roberston et al, 2015). The assessing clinician may need to consider the role of factors such as seizure frequency, peri-ictal events and the role of anti-epileptic drugs (AEDs) additionally in their formulation (Kerr et al, 2016).…”
Section: Seizures Can Present As Symptoms Of Mental Illnessmentioning
confidence: 99%